PEMANFAATAN KOMUNIKASI DARI MULUT KE MULUT (WORD OF MOUTH) DALAM BISNIS AYAM PANGGANG GANDU - Subiyantoro; Netty Lisdiantini; Agustinus Doedyk Setiyawan (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2019)
The strategy used by the Gandu Roast Chicken business actors in building consumer perception is done by forming positive quality perceptions through the attributes of roasted chicken products, especially in terms of quality, features, price, and service excellence. The excellence of the products and services presented has made consumers satisfied and finally shared their experiences with others. The occurrence of oral, written, and electronic communication through WOM (word of mouth) and E-WOM (electronic word-of-mouth) between communities encourages the formation of brand identity and gives rise to brand image, positive perceptions in the minds of consumers related to Chicken Roasted Gandu. Whether we realize it or not, consumers who are satisfied with the quality of products and services have promoted it, recommending it to others around them. Information about excellence that is spread through E-WOM obtained from others has a strong influence. Recommendations from other consumers are more reliable, because they are independent, non-commercial, honest, and have no relationship with business actors. Besides that, the range of its spread is also very wide, because it takes place on social networking sites of the internet and social media that have no geographical restrictions, time or social ties, so before deciding to buy a product, consumers can get many opportunities to exchange information easily and effectively. Utilization of E-WOM can increase sales significantly in a relatively fast time